2016
DOI: 10.1088/0957-4484/27/38/385103
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of anti-inflammatory agent into mesoporous silica

Abstract: The unique properties of macroporous, mesoporous, and microporous systems, including their ability to accommodate molecules of different sizes inside their pores and to act as drug delivery systems, have been the object of extensive studies. In this work, mesoporous silica with hexagonal structure was obtained by template synthesis via the sol-gel process. The resulting material was used as support to accommodate the anti-inflammatory agent indomethacin. The alkaline route was used to prepare the mesoporous si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…However, on amino functionalization, a relatively prolonged release of the drug was observed due to the strong interaction between the amino groups of silica surface and carboxyl groups of ibuprofen [ 202 ]. Other similar studies were carried out to successfully deliver aspirin [ 155 ] and indomethacin [ 203 ] using MSNs with high drug loading and slow release profile.…”
Section: Applications Of Msns In Drug Deliverymentioning
confidence: 99%
“…However, on amino functionalization, a relatively prolonged release of the drug was observed due to the strong interaction between the amino groups of silica surface and carboxyl groups of ibuprofen [ 202 ]. Other similar studies were carried out to successfully deliver aspirin [ 155 ] and indomethacin [ 203 ] using MSNs with high drug loading and slow release profile.…”
Section: Applications Of Msns In Drug Deliverymentioning
confidence: 99%
“…Surface functionalization using aminosilanes is one of the most commonly used methods for post-synthesis functionalization of mesoporous materials. Grafting aminosilanes to the surface of different porous materials has been executed to improve their performance in CO 2 sorption [23,24], drug delivery [25,26], and catalysis [27]. Surface modification also allows the drug loading and release profile of porous materials to be tuned [28].…”
Section: Introductionmentioning
confidence: 99%
“…Braz et al loaded MSN with the anti-inammatory drug indomethacin and showed that the MSN-drug complex signicantly lowered the in vitro cytotoxicity compared to the free form of the drug. 81 These MSN-based systems can be further improved, for example by using coatings such as ethylcellulose, which prolongs the drug release. 82 Additionally, it can be modied for stimuli-responsive drug release by e.g.…”
Section: Silicamentioning
confidence: 99%